Ejecución presupuestaria del Gobierno Autónomo Descentralizado de la Parroquia Febres Cordero del cantón Babahoyo de los periodos 2019-2020. - Jiménez Álvarez, Paola Roxana (2022)
The Autonomous Decentralized Rural Parish Government of Febres Cordero is a public institution whose purpose is to ensure the welfare and social security of the community, in addition to providing services for the development and growth of the parish, through the principles of equity, democracy, solidarity, transparency, integrity and diversity, and thus citizens have a better quality of life. In order to analyze the variation registered in the budget of the institution, the present case study is called "Budget Execution of the Decentralized Autonomous Government of the Febres Cordero Parish of the Babahoyo Canton for the periods 2019 and 2020". This research is part of the inductive, deductive and descriptive methodology, which allow the application of research techniques such as observation and interview, with the purpose of collecting information from primary sources to know and analyze that the codified assignments have been executed in its entirety. and realize the destinations of said resources, in addition to the variations they presented.